Penguatan Nilai-nilai Aswaja An Nahddliyah di Majlis Taklim Nurul Hidayah Kelurahan Tosaren Kota Kediri - Siti Mahmudah; Naila Azahra (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The strengthening of Ahlussunnah wal Jama’ah (Aswaja) An-Nahdliyah values at the grassroots level is a vital strategy to counter ideological threats in the digital era. This community service program was conducted at Majlis Taklim Nurul Hidayah, Tosaren Subdistrict, Kediri City, whose members consist primarily of Muslimat women. The goal was to improve moderate religious understanding based on Aswaja through educational, participatory, and tradition-based Islamic approaches. The methods included interactive lectures, group discussions, book reading sessions, and practical religious rituals such as tahlil, shalawat, and istighotsah. The results showed a significant increase in participants' understanding of core Aswaja principles such as tawassuth (moderation), tasamuh (tolerance), tawazun (balance) and i’tidal (justice). The program also successfully fostered critical awareness among participants regarding misleading religious content circulating online. Key supporting factors included high participant enthusiasm, strong NU cultural roots, and support from local religious leaders. Nevertheless, challenges remain, including limited access to user-friendly Aswaja literature and the need for sustained mentoring. This activity affirms the potential of majlis taklim as centers of religious moderation at the community level. Similar programs are recommended to be replicated with sustainable support across sectors.